Fundamentals of Chalcopyrite Dissolution in Alkaline Glycine Solutions - O'Connor, Gregory Michael (Curtin University, 2018)
The slow leach rate of copper from chalcopyrite in acid solutions has often been attributed to the formation of a poorly soluble “passive” layer on the surface. For this study, it has been shown that no such passive layer exists in alkaline glycine solutions. Surface analyses have shown these species exist, but are not passivating. The leach rate is instead determined by the electronic structure of chalcopyrite.